Effects of light intensity on the distribution of anthocyanins in Kalanchoe brasiliensis Camb. and Kalanchoe pinnata (Lamk.) Pers - Cruz,Bruna P. (2012)
This paper compares two medicinal species of Kalanchoe, which are often used interchangeably by the population, regarding the distribution of anthocyanins under the influence of four luminosity levels for 6 months. For the morphoanatomical analysis, the 6th stem node of each plant was sectioned. Usual histochemical tests revealed the presence of anthocyanins by cross sections of the stems, petioles and leaf blades. The petioles and leaf blades were submitted to the extraction with acidified methanol, and the anthocyanins were quantified by spectrophotometric readings. At the macroscopic level, it was noticed for both species a higher presence of anthocyanins in stems and petioles of plants under full sunlight. The microscopy of K. brasiliensis stems evidenced the deposition of anthocyanins in the subjacent tissue to the epidermis and cortex, which increased with light intensity. In K. pinnata a subepidermal collenchyma was observed, which interfered in the visualization of anthocyanins. In petioles and leaf blades of K. brasiliensis the deposition of anthocyanins was peripheral, and in K. pinnata it was also throughout the cortex. The quantification of anthocyanins in petioles showed in 70% of light higher averages than in 25%, but in leaf blades there were no significant results. This study contributes to the pharmacognosy of Kalanchoe and it is sustained by the description of flavonoids as biological markers of the genus.